Development of a SAW-Based Student Registration Website at SD Negeri 6 Tondano (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2026)
The development of a web-based information system for the new student registration process and school profile at SDN 6 Tondano was carried out using a research and development (R&D) approach. This system is designed to streamline administrative processes, improve efficiency, and enhance the transparency of school services. Key features include an informative homepage, a user-friendly registration page, and a student and teacher data management module integrated with the Simple Additive Weighting (SAW) algorithm to support an objective and fair student selection process. The use of the SAW method allows for the combination of various assessment indicators into a single comprehensive score that assists the school in making decisions regarding the selection of prospective students. The implementation of this system is expected to improve operational efficiency, strengthen communication between schools and parents, and support digital transformation in the elementary education sector. Research results indicate that the developed system effectively and sustainably meets schools’ needs and contributes to the delivery of modern and reliable educational services.